Death, dying and donation: organ transplantation and the diagnosis of death. Issue 2 (1st April 2002) - Kerridge, I H; Saul, P; Lowe, M; McPhee, J; Williams, D
Abstract : Refusal of organ donation is common, and becoming more frequent. In Australia refusal by families occurred in 56% of cases in 1995 in New South Wales, and had risen to 82% in 1999, becoming the most important determinant of the country's very low organ donation rate (8.9/million in 1999). Leading causes of refusal, identified in many studies, include the lack of understanding by families of brain death and its implications, and subsequent reluctance to relegate the body to purely instrumental status. It is an interesting paradox that surveys of the public continue to show considerable support for organ donation programmes—in theory we will, in practice we won't (and don't). In this paper we propose that the Australian community may, for good reason, distrust the concept of and criteria for "whole brain death", and the equation of this new concept with death of the human being. We suggest that irreversible loss of circulation should be reinstated as the major defining characteristic of death, but that brain-dead, heart-beating entities remain suitable organ donors despite being alive by this criterion. This presents a major challenge to the "dead donor rule", and would require review of current transplantation legislation. Brain dead entities are suitable donors because of irreversible loss of personhood, accurately and robustly defined by the current brain stem criteria. Even the dead are not terminally ill any more. 1